BNT162b2 COVID-19 vaccine and correlates of humoral immune responses and dynamics: a prospective, single-centre, longitudinal cohort study in health-care workers. Issue 9 (September 2021) - Lustig, Yaniv; Sapir, Einav; Regev-Yochay, Gili; Cohen, Carmit; Fluss, Ronen; Olmer, Liraz; Indenbaum, Victoria; Mandelboim, Michal; Doolman, Ram; Amit, Sharon; Mendelson, Ella; Ziv, Arnona; et al.
Summary: Background: Concurrent with the Pfizer–BioNTech BNT162b2 COVID-19 vaccine roll-out in Israel initiated on Dec 19, 2020, we assessed the early antibody responses and antibody kinetics after each vaccine dose in health-care workers of different ages and sexes, and with different comorbidities. Methods: We did a prospective, single-centre, longitudinal cohort study at the Sheba Medical Centre (Tel-Hashomer, Israel). Eligible participants were health-care workers at the centre who had a negative anti-SARS-CoV-2 IgG assay before receiving the first dose of the intramuscular vaccine, and at least one serological antibody test after the first dose of the vaccine. Health-care workers with a positive SARS-CoV-2 PCR test before vaccination, a positive anti-SARS-CoV-2 IgG serology test before vaccination, or infection with COVID-19 after vaccination were excluded from the study. Participants were followed up weekly for 5 weeks after the first vaccine dose; a second dose was given at week 3. Serum samples were obtained at baseline and at each weekly follow-up, and antibodies were tested at 1–2 weeks after the first vaccine dose, at week 3 with the administration of the second vaccine dose, and at weeks 4–5 (ie, 1–2 weeks after the second vaccine dose). Participants with comorbidities were approached to participate in an enriched comorbidities subgroup, and at least two neutralising assays were done during the 5 weeks of follow-up in those individuals. IgG assays were done for the entire study population, whereas IgM, IgA, and neutralising antibody assays were done only in the enriched comorbidities subgroup. Concentrations of IgG greater than 0·62 sample-to-cutoff (s/co) ratio and of IgA greater than 1·1 s/co, and titres of neutralising antibodies greater than 10 were considered positive. Scatter plot and correlation analyses, logistic and linear regression analyses, and linear mixed models were used to investigate the longitudinal antibody responses. Findings: Between Dec 19, 2020, and Jan 30, 2021, we obtained 4026 serum samples from 2607 eligible, vaccinated participants. 342 individuals were included in the enriched comorbidities subgroup. The first vaccine dose elicited positive IgG and neutralising antibody responses at week 3 in 707 (88·0%) of 803 individuals, and 264 (71·0%) of 372 individuals, respectively, which were rapidly increased at week 4 (ie, 1 week after the second vaccine dose) in 1011 (98·4%) of 1027 and 357 (96·5%) of 370 individuals, respectively. Over 4 weeks of follow-up after vaccination, a high correlation ( r =0·92) was detected between IgG against the receptor-binding domain and neutralising antibody titres. First-dose induced IgG response was significantly lower in individuals aged 66 years and older (ratio of means 0·25, 95% CI 0·19–0·31) and immunosuppressed individuals (0·21, 0·14–0·31) compared with individuals aged 18·00–45·99 years and individuals with no immunosuppression, respectively. This disparity was partly abrogated following the second dose. Overall, endpoint regression analysis showed that lower antibody concentrations were consistently associated with male sex (ratio of means 0·84, 95% CI 0·80–0·89), older age (ie, ≥66 years; 0·64, 0·58–0·71), immunosuppression (0·44, 0·33–0·58), and other specific comorbidities: diabetes (0·88, 0·79–0·98), hypertension (0·90, 0·82–0·98), heart disease (0·86, 0·75–1·00), and autoimmune diseases (0·82, 0·73–0·92). Interpretation: BNT162b2 vaccine induces a robust and rapid antibody response. The significant correlation between receptor-binding domain IgG antibodies and neutralisation titres suggests that IgG antibodies might serve as a correlate of neutralisation. The second vaccine dose is particularly important for older and immunosuppressed individuals, highlighting the need for timely second vaccinations and potentially a revaluation of the long gap between doses in some countries. Antibody responses were reduced in susceptible populations and therefore they might be more prone to breakthrough infections. Funding: Sheba Medical Center, Israel Ministry of Health.